Tuberculosis in foreign students in Japan, 2010-2014: a comparison with the notification rates in their countries of origin - Masaki Ota; Kazuhiro Uchimura; Seiya Kato (World Health Organization Regional Office for the Western Pacific, 2016)
This study characterizes the foreign students with tuberculosis (TB) registered in Japan from 2010 to 2014 and compares their TB notification rates with those in their countries of origin. The TB notification rates in foreign students were retrieved from the National Epidemiological Surveillance of Infectious Disease system in Japan. National TB notification data from 16 countries and areas were extracted from the World Health Organization's and the official health websites of the countries and areas. There were 1128 foreign students in Japan who developed TB between 2010 and 2014; nearly half of the cases were from China (n = 530, 46.9%), and 688 (61.0%) were male with a median age of 23 years. The TB notification data for foreign students were highest in students from the Philippines (675/100 000 person years, 95% confidence interval: 372-977). The notification rates in foreign students from seven countries were significantly higher than the average notification rate in their countries of origin (China, Indonesia, Mongolia, Myanmar, Nepal, the Philippines and Viet Nam). The Republic of Korea and Taiwan, China had significantly lower rates in foreign students than in their countries of origin. The notification rates for foreign students in Japan may reflect a more accurate risk of developing TB among the immigrants to Japan than the TB notification rates in their countries of origin. These results may be helpful to identify the immigrants' countries/areas of origin with the necessity of pre-entry TB screening.